Book and Paper Conservation MA Degree Theses — 1992–2019. Camberwell College of Arts, University of the Arts London. Issue 1 (2nd October 2021) - Cuming, Jocelyn; Velios, Athanasios
ABSTRACT: Conservation education in Books and Paper at Camberwell College of Arts formally started in 1970, having grown out of a strong British tradition in bookbinding and typography dating as far back as 1904. This is the complete list of the Book and Paper MA degree works from 1992 to 2019, when the course was discontinued.